(untitled) (ENTHYMEMA, 2023)
Luisa de Carvajal (1566–1614), Spanish mystic and Catholic missionary, wrote around 50 spiritual poems. This paper examines the English translation of one of them, the ballad “En una Graciosa isleta”, text chosen by Georgiana Fullerton to bring closure to her Life of Luisa de Carvajal (1873). This biography, based on a previous one by Luis Muñoz, published in 1632, presents the poet’s life as an example of sacrifice in the context of the reformist persecutions of Catholics. The translated poem is examined from two perspectives: firstly, an inquiry into the motivations and publishing circumstances around the translation of the text in the second half of the 19th century; secondly, an internal text analysis of the versification and rhetorical devices conveying Carvajal mystical vision.